ʻUbaidullah Sindhī aur unke nāqid / Sʻaīd Aḥmad Akbarābādī - Saʻīd Aḥmad Akbarābādī, 1908- (SAMP early 20th-century Indian books project ;, 1946)
Critical biography on the life & work of Maulana Ubaidullah Sindhi.